Pemetaan Potensi Budidaya Perikanan Kabupaten Lamongan 2024 - Rosa Zahrina; Rohmatin Agustina; Arini Roro Anggun (Jurnal Ilmu Pertanian dan Perikanan, 2025)
Lamongan Regency is one of the regions with significant potential for aquaculture development in East Java. This study aims to map the potential of aquaculture in Glagah, Turi, and Karangbinangun Districts as a basis for sustainable aquaculture development planning. The methods used included primary data collection through field observations and interviews with fish farmers, as well as secondary data obtained from the Lamongan Regency Fisheries Office. The research stages consisted of identifying geographical conditions, aquaculture land area, leading commodities, number of aquaculture households, and cultivation systems applied in each district. The results showed that Glagah District has high potential for brackish water aquaculture with milkfish and vannamei shrimp as the main commodities. Turi District is dominated by freshwater aquaculture such as catfish and tilapia using traditional systems, while Karangbinangun District has developed semi-intensive to intensive aquaculture systems. The main constraint faced by farmers is the limited availability of production inputs, particularly subsidized fertilizers, which increases production costs. In conclusion, aquaculture potential mapping is essential as a foundation for policy formulation and the development of more effective and sustainable aquaculture in Lamongan Regency.